The Psychosocial Dynamics Behind Turkey's Withdrawal from The Istanbul Convention: A Study of Cultural Values, Collective Identity, and Resistance to Global Gender Norms - Haris Munandar; Rania Nabilla Putri (International Journal of Universal Education, 2026)
Background: Turkey's withdrawal from the Istanbul Convention in March 2021 marked a striking reversal, as Turkey had been the first country to ratify this Council of Europe treaty combating violence against women in 2012, despite persistently high femicide rates nationwide. This study examines the psychosocial factors underlying Turkey's decision, focusing on the interplay between cultural values, collective identity, and resistance to global gender norms. Method: Employing a qualitative explanatory approach through library research, data were collected from academic literature, official documents, institutional reports, media publications, and political statements. The analysis applies Richard Snyder's Decision-Making Theory, examining internal settings (society and human environment), social structure and behaviour (common values, institutional patterns, and social processes), and external settings (other cultures and societies). Result and Discussions: Findings reveal that Turkey's withdrawal was predominantly driven by domestic factors, particularly Islamic teachings and traditional cultural values concerning gender roles, family honour, and patriarchal structures. The conservative public and ruling AKP party, led by President Erdoğan, shared a common value orientation perceiving the convention as threatening traditional family values and normalizing homosexuality. Anti-gender movements in Turkey, inspired by similar movements in Central and Eastern Europe, amplified these concerns. Turkey's growing de-Europeanization and frustration with EU accession processes further reinforced the rejection of externally imposed norms. This withdrawal represents a complex psychosocial phenomenon where cultural identity, religious values, collective resistance, and political calculations converged. The decision reflects broader global contestation over gender equality norms, highlighting tensions between universal human rights frameworks and locally embedded cultural-religious values. This study contributes to understanding how psychosocial dynamics shape foreign policy decisions in culturally conservative contexts.